Synthesis of pyridazine derivatives by Suzuki-Miyaura cross-coupling reaction and evaluation of their optical and electronic properties through experimental and theoretical studies - Fernandes, Sara S. M. (2019)
The authors thank the Fundacao para a Ciencia e Tecnologia (Portugal) and FEDER-COMPETE for financial support through the Centro de Quimica and Centro de Fisica das Universidades do Minho e do Porto in the framework of the Strategic Funding (UID/QUI/0686/2016 and UID/FIS/04650/2013). Thanks are also due to Fundacao para a Ciencia e Tecnologia (FCT) for a Ph.D. grant to Sara S. M. Fernandes (SFRH/BD/87786/2012). This work was also supported by the Associated Laboratory for Sustainable Chemistry-Clean Processes and Technologies-LAQV which is financed by Portuguese national funds from FCT/MEC (UID/QUI/50006/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265). The NMR spectrometers are part of the National NMR Network (PTNMR) and are partially supported by Infrastructure Project No 022161 (co-financed by FEDER through COMPETE 2020, POCI and PORL and FCT through PIDDAC). The pulsed laser system was acquired within the framework of the grant (PTDC/CTM/105597/2008) from the Fundacao para a Ciencia e Tecnologia (FCT) with funding from FEDER-COMPETE.